-78+4x=42-8x

Simple and best practice solution for -78+4x=42-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -78+4x=42-8x equation:


Simplifying
-78 + 4x = 42 + -8x

Solving
-78 + 4x = 42 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-78 + 4x + 8x = 42 + -8x + 8x

Combine like terms: 4x + 8x = 12x
-78 + 12x = 42 + -8x + 8x

Combine like terms: -8x + 8x = 0
-78 + 12x = 42 + 0
-78 + 12x = 42

Add '78' to each side of the equation.
-78 + 78 + 12x = 42 + 78

Combine like terms: -78 + 78 = 0
0 + 12x = 42 + 78
12x = 42 + 78

Combine like terms: 42 + 78 = 120
12x = 120

Divide each side by '12'.
x = 10

Simplifying
x = 10

See similar equations:

| -3(2x+4)+1=19 | | -8x-65=103+4x | | 60s=50 | | .03x+.4=8 | | -18-4x=16-6x | | -7x+11+2x=-4 | | -6x-8=13-7x | | 60s+6=56 | | W=2YZ+2YXfory | | h=16t^2+1444 | | 1.298=((x^3)-1.298x) | | -73-3x=71+6x | | -2+3x=3x+6+x | | 6x-1=-x-29 | | 3x^3-15x^2+12x=0 | | -6x-76=64+x | | 6x-1=x-29 | | -2x-10=11-x | | 2q^2+10qb+8b^2=0 | | 9(30-12t)=8(6+9t)-24t | | 3.56x+7.56x+9.12=50.85 | | 6x+3+4=10 | | 3x^2+x=114 | | q^3-b^3=0 | | 16.95+.05x=22.95+0.2x | | -73+4x=96-9x | | 5x^2-11x-124=0 | | 9.1x=-34.58 | | 3b+20=56 | | 6x^2-(10-3a)x+(2-5a)= | | 4.28-0.4j=1.48 | | -9-(-4)+(-5)= |

Equations solver categories